High IgG4 serum concentration is associated with active Graves orbitopathy - Olejarz, Michał; Szczepanek-Parulska, Ewelina; Ostałowska-Klockiewicz, Anna; Antosik, Patrycja; Sawicka-Gutaj, Nadia; Helak-Łapaj, Celina; Stopa, Marcin; Ruchala, Marek (Frontiers in Endocrinology, 2023)
Background: The aim of the study was to evaluate the differences in clinical profile, laboratory parameters, and ophthalmological signs, and symptoms between patients with high IgG4 Graves orbitopathy and patients with normal IgG4 Graves orbitopathy. Methods: This was a prospective observational study. We recruited adult patients with Graves Orbitopathy(GO) referred to our clinic for further diagnostics and treatment. Eventually, 60 patients with GO were enrolled in the study. All patients underwent ophthalmological assessment, magnetic resonance imaging (MRI) of the orbits, and laboratory tests, including IgG4 serum concentration measurement. High IgG4 GO was diagnosed if the IgG4 concentration exceeded 135 mg/dl. We used both the clinical activity score (CAS) and magnetic resonance imaging (MRI) to assess the activity of GO. Eventually, active GO was defined according to MRI results. Results: Among 60 GO patients, 15 (25%) patients had elevated IgG4 levels. Patients in the high IgG4 group had a higher prevalence of active GO by MRI than patients with normal IgG4 (100% vs. 64.44%, P=0.006). They also had a higher eosinophile count in peripheral blood, a lower bilirubin level, a more frequent lower eyelid retraction, and a lower prevalence of glaucoma. There were no statistically significant differences between the groups in CAS. Patients with active GO, had higher median IgG4 level [89.95 (55.48; 171.1) vs 43.45 (32.48; 49.68) mg/dl, P<0.001]. The receiver operating characteristic (ROC) analysis for IgG4 as a marker of active GO revealed the following results: AUC 0.848 for the cut-off value of 54.2 mg/dl, sensitivity 79.5%, specificity 87.5%, positive predictive value 94.6%, negative predictive value 59.1%. . Conclusions: We demonstrated that IgG4 is a marker of GO activity. Certain differences in the clinical profile of patients with high IgG4 GO, and normal IgG4 GO were observed. More data is needed to establish whether patients with high IgG4 GO are GO patients with particularly active disease or actually represent a distinct clinical entity related to IgG4-Related Disease.